An Alternative Regulation of Compensation Mechanisms for Electric Energy Transgressions of Service Quality Limits in Dispersed and Seasonal Areas - Julio A. de Bitencourt; Daniel P. Bernardon; Henrique S. Eichkoff; Vinicius J. Garcia; Daiana W. Silva; Lucas M. Chiara; Renan L. B. Gomes; Sebastian A. Butto; Solange M. K. Barbosa; Alejandre C. A. Pose (Energies, 2023)
The evaluation of the quality of electric power distribution services in Brazil is regulated and monitored by the National Electric Energy Agency ANEEL, which uses metrics related to the duration frequency of power interruptions that occur in the power utilities’ networks. The methodology applied by the agency to establish financial compensation due to violations of the quality standards does not take into consideration the consumers’ production industry when establishing compensation for the transgression of service quality indicators. This study will analyze a case study of a group of industrial consumers linked to agribusiness in the southern region of Brazil, which have strongly seasonal use of distribution networks and are scattered in large, dispersed areas. Based on the evaluation of the impact of service quality indicators on financial compensation, a regulatory mechanism is proposed in the form of an interruptible tariff duly quantified in the form of a non-linear programming problem to find a discount range for uninterruptible tariffs. The results obtained with the real data for the group of irrigating consumers demonstrate the feasibility regarding the application of the proposed approach, whether due to the discounts offered or even the repercussions of the calculated financial amounts.